2018
DOI: 10.3892/ol.2018.9662
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin‑induced promoter hypermethylation of the mammalian target of rapamycin gene in multiple myeloma cells

Abstract: Curcumin, a polyphenol derived from the rhizome of Curcuma, is a potential tumor inhibitor through affecting signaling pathways and epigenetic regulation. The mammalian target of rapamycin (mTOR) gene serves a crucial role in the carcinogenesis of multiple myeloma. The curcumin-induced epigenetic regulation of mTOR, including promoter DNA methylation in multiple myeloma, has not yet been fully elucidated. In the present study, antitumor effects of curcumin were investigated in RPMI-8226 and NCI-H929 cells usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
(31 reference statements)
1
12
0
Order By: Relevance
“…However, with regard to multiple myeloma cells, it has recently been reported that curcumin-induced promoter methylation to the mTOR gene was associated with a corresponding downregulation of its expression. The authors suggested that curcumin-induced hypermethylation of mTOR may be associated with the upregulation of DNMT3a and DNMT3b (47). Here, we found that curcumin downregulated TET1 in T47D and upregulated DNMT3a and DNMT3b in T47D and HCC-38 cells.…”
Section: Discussionsupporting
confidence: 64%
“…However, with regard to multiple myeloma cells, it has recently been reported that curcumin-induced promoter methylation to the mTOR gene was associated with a corresponding downregulation of its expression. The authors suggested that curcumin-induced hypermethylation of mTOR may be associated with the upregulation of DNMT3a and DNMT3b (47). Here, we found that curcumin downregulated TET1 in T47D and upregulated DNMT3a and DNMT3b in T47D and HCC-38 cells.…”
Section: Discussionsupporting
confidence: 64%
“…However, curcumin is known as a PAINS (pan-assay interference compounds) and thus its bioactivities have to be analyzed with care ( Nelson et al, 2017 ). A recent report indicated an inhibition of the growth of myeloma cells by curcumin with an IC 50 value of 10 µM ( Chen et al, 2019a ). Curcumin has been reported to induce cell cycle arrest at G1/S phase in androgen-sensitive prostate cancer LNCaP cells and androgen insensitive PC-3 cells ( Srivastava et al, 2007 ).…”
Section: Dna Methyltransferases Inhibitors ( Figure 1 mentioning
confidence: 99%
“…Methylation level of CMT2 was decreased in AZD + RAP treated sample, implying that TOR inhibition may activate DRM2 or CMT2 to maintain CHH methylation level. Interestingly, our study showed that TOR regulated genome DNA methylation to control plant growth in Arabidopsis, while curcumin induced the promoter hypermethylation of mTOR gene in myeloma cells (Chen et al, 2019), suggesting that TOR had a feedback regulation mechanism in the process of regulating DNA methylation. The detailed regulatory mechanisms of TOR and DNA methyltransferases still need further study in the future.…”
Section: Discussionmentioning
confidence: 76%